ENDOSCOPIC ULTRASOUND INVESTIGATION FOR NEUROENDOCRINE PANREATIC NEOPLASMS DIAGNOSIS - N. S. Ryabin; M. I. Bykov; A. N. Katrych; V. V. Schava (Инновационная медицина Кубани, 2019)
Endoscopic ultrasound diagnosis occupies an important role in neuroendocrine tumor diagnosis. Key indicators for diagnostic efficiency of this method regarding a tumor nosology are presented in the present article. We described results of the authors; investigations on ultrasonography for neuroendocrine tumor differentiated diagnosis. Possible mistakes in diagnosis of existing neuroendocrine tumors and a study algorithm are analyzed during endoscopic ultrasound investigation.